Identification of Salmonella spp. Bacteria in Fishery Products at the Testing Laboratory of the Marine and Fishery Products Quality Control and Supervision Agency (BPPMHKP) Surabaya II - Elysia Zahra Helga Sandita; Eva Agustina; Zaki Muhammad Wijaya; Anita Tri Widyayanti (Pro-Life, 2025)
Fish is a crucial source of animal protein and a primary commodity in the fisheries industry. Fishery products include fresh fish and frozen fish. Fish is a type of food that is susceptible to biological damage and decay. One of the causes of spoilage and microbial contamination in fishery products by pathogenic bacteria is Salmonella spp. The purpose of this study was to determine the results of the identification of Salmonella spp. in fishery products at the Testing Laboratory of the Fisheries Product Quality Control and Supervision Agency (BPPMHKP) Surabaya II. This study employed the SNI ISO 6579-1:2017 reference method and was analyzed descriptively to determine the presence of Salmonella spp.. Based on the identification results, out of the four samples tested, only one sample was positive for Salmonella spp., namely dried himego products.